Analisis Statistik Hubungan Tingkat Pengetahuan Terhadap Perilaku Swamedikasi Gastritis - Mustofani, Dian; Hariyani, Hariyani (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2024)
Self-medication or self-medication is an action taken by a person to treat minor health problems independently without consulting a doctor. Gastritis is a condition when the amount of stomach acid increases, causing stomach irritation. Typical symptoms of gastritis include pain and tenderness in the pit of the stomach even though you have previously eaten. If the pain only occurs before eating and then disappears after eating, this indicates excessive stomach acid production and you are not suffering from gastritis. Usually gastritis is caused by an open wound in the inner lining of the stomach. This research aims to apply statistical analysis of the Spearman rank test to determine the relationship between level of knowledge and gastritis self-medication behavior. The research method used is descriptive analytic using a cross-sectional design, using a purposive sampling method. The number of samples used in this research was 127 people who met the inclusion criteria. The statistical data analysis used was the Spearman Rank test. Where the analysis shows the results of the Spearman Rank test, a significant value of 0.000 was obtained.